Sicherheitsrisiko "Kunst im Kreisverkehr". - Morlock, Gero (Kirschbaum, 2013)
Due to increasing traffic congestion road maintenance services are growing in importance. Klein thus argues that the sharp rise in road use results in an increasing demand for road maintenance and upkeep. On the one hand, this raises the risk of traffic disruptions caused by maintenance service; according to Durth short term maintenance activities account for 25 percent of the duration of traffic jams on German freeways. On the other hand, increasing traffic congestion complicates the planning, coordination, and execution of maintenance activities on the road. Therefore measures have to be developed that lead to more effective operation services and thus to a reduction of traffic disruptions. In doing so it is imperative to take into account the high physical and mental stress levels characterizing the position of road maintenance worker. In order to improve the situation with regard to economic matters, the processes occuring in the field of road maintenance, including physical and mental stresses, thus have to be optimized.
Process Optimization for Summer Road Maintenance.
Keywords: Verkehr; Verkehrsanlage; Verkehrsunfall; Unfallverhütung; Verkehrsknoten; Straßeninstandhaltung; Verkehrssicherheit; Kunst im öffentlichen Raum; Kreisverkehr